On nontuberculous mycobacteria in human alveolar macrophages - João, Inês (2021)
Background: Despite growing relevance of nontuberculous mycobacteria (NTM) infections, namely pulmonary infections, accurate data on incidence and pathogenesis is lacking. Iintracellular persistence of three NTM species in a human alveolar macrophages model. The contribution of particular innate immune mechanisms and NTM genomes to mycobacteria intracellular fate were investigated. Materials/methods: M.smegmatis mc2155, reference strains (M.avium ATCC25291; M.fortuitum ATCC6841) and clinical isolates (M.avium 60/08; M. fortuitum 747/08) were used. Mycobacteria intracellular persistence was assessed via: 4x104 THP-1 cells platted/well and incubated for 72h with 100nM PMA. Then fresh medium without PMA was added and the cells incubated for further 24h. The cells were infected for 1h (fast) or 3h (slow growers). Intracellular persistence was evaluated by CFU enumeration at different time points. NO production was evaluated using the Griess reagent, phagosome acidification and apoptosis was followed by confocal microscopy. Persistence ability of mycobacteria at different pHs was evaluated using BACTEC-MGIT960. NTMs virulence factors were characterized by whole-genome sequencing.